Fatigue and health-related quality of life in patients with pulmonary sarcoidosis treated by oral Corticosteroids - Aggarwal, Ashutosh Nath; Sahu, Kamal Kant; Gupta, Dheeraj (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: It is not clear how well sarcoidosis-associated fatigue improves with definitive therapy. Objective: To evaluate improvement in fatigue in patients of sarcoidosis receiving oral corticosteroid therapy, and correlate it with clinical recovery and change in health-related quality of life (HRQL).Methods: We studied 51 newly diagnosed adult patients of pulmonary sarcoidosis. Sarcoidosis Health questionnaire (SHQ) was used to assess HRQL. Fatigue was evaluated using Fatigue Assessment Scale (FAS). All patients received six month treatment with oral prednisolone, and SHQ and FAS were administered before initiation and after completion of treatment. Baseline and post-treatment scores were compared and a 4-point change in FAS scores considered clinically significant. Results: All patients improved clinically and radiologically with therapy. Body aches, however, persisted in 12 of 28 (42.9%) patients having this symptom at baseline. 33 patients (64.7%) had pre-treatment fatigue (FAS >=22), of which seven (13.7%) were severely fatigued (FAS score >=35). Of them 21 (63.6%) and 4 (12.1%) patients respectively showed improvement and deterioration in FAS score by >4 points. Only five of 18 patients with baseline FAS score 4 point score increment after treatment, and four of them developed fatigue during therapy. All patients with baseline severe fatigue improved. Overall, FAS scores, and all SHQ domain scores, significantly improved with treatment. Conclusions: Both fatigue as well as HRQL improved significantly, and largely parallelly, with treatment for sarcoidosis. Persistence of fatigue, or new onset fatigue, may be encountered during treatment, possibly as an adverse effect of corticosteroid therapy.